ANALISIS BAHAYA PADA PEKERJA BAGIAN WORKSHOP PT. X MEDAN TAHUN 2015 - siti widya nazhrah; eka lestari mahyuni; isyatun mardiyah syahri (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT All the work has been helped by tools that can facilitate the work of man, for example the engine, but can make a considerable profit, but also cause losses due could be damaged and cause accidents. Accident prevention can be done by analyzing any existing hazards in the working environment. One method is to conduct a hazard analysis Hazard and Operability Study (HAZOPS). HAZOPS is a method of identifying and analyzing the danger of a process unit when deviating from it should be. This research is a descriptive survey that describes the results of hazard identification and analysis using method HAZOPS in a work process. The object under study is contained in the workshop processes ie loading / unloading, disassembly, machine repair, engine repair, washing, and painting at the PT. X 2015. These results indicate that the hazards are in the process of loading / unloading is working at height and straps are not unstable. In the process there is the danger of slippery floor disassembly, the strap is not stable, less control of cranes and forklifts. In the process there is the danger of the machine repair welding and tapping. In the process there is the danger of engine repair and unsafe ways of working as well as working at height. In the process of washing the danger of contact with diesel and slippery floors. In the painting process are inhaled paint and fire hazards. Researcher suggests to the management of PT. X to keep increasing the work safety and healthy by controlling various hazard in each process at workshop.